Thermo-economic turbine cycle heat rate performance analysis of coal fired power plant - Jasbeer Singh, Manmit Singh (2022)
Coal Fired Power Plants (CFPP) are the backbone of the power generation sector in Malaysia, providing approximately 40% of the national energy demand. The efficient and optimum operations of the plants are vital to minimise the cost of producing energy per unit to ensure the plant remains profitable and sustainable to operate. Subcritical CFPP generally have an efficiency of 33-37% during the commissioning performance test. However, as the plant ages, the efficiency and Heat Rate (HR) deteriorate over time due to ageing and operational deviations from design values causing financial losses and since majority of CFPPs are base load plants producing maximum power output, the potential performance improvement is more significant. Since majority of the subcritical CFPP units only have 10 years remaining on Power Purchase Agreement (PPA), it is not viable to consider major retrofitting due to poor return on investment (ROI) thus this study focuses only on economic analysis of the CFPP based on operational aspects. The main objective of this study is to investigate the Turbine Cycle Heat Rate (TCHR) by developing a numerical mathematical model which enables the evaluation of the TCHR which forms the basis for conducting economic analysis of CFPP performance. The model is developed by utilizing energy and mass balance relationships of the turbine cycle which are validated against heat balance diagram of a 700MWn CFPP. The usage of actual plant data improves the accuracy and confidence level of the results. In order to obtain the HR of a CFPP, the TCHR has to be evaluated first by conducting energy and mass balance of key components in the turbine cycle such as the Low-Pressure Heaters (LPH), High Pressure Heaters (HPH) and deaerator. The model is able to determine the extraction steam flows of the LPH, HPH and deaerator and subsequently the feedwater flow as these flows are not available on the Distributed Control System (DCS) but are required to evaluate the TCHR. The plant operational data such as pressure and temperature of extraction steam are readily available in the Plant Information (PI) system from which the data is extracted. In essence, the model enables comparison of plant HR at various operating loads against available commissioning data thus the economic analysis is conducted and it is determined that at the operating baseload of 729 MWg, there is a HR deviation of -1,135 kJ/kWh which inevitably causes daily losses of RM240,447 or USD 60,112. The developed model is also able to evaluate the daily losses at lower operating loads as the plant is now in transition to cyclic loads operation. At lower loads of 431 MWg, the daily losses amount to RM 125,767 or USD 31,442. The second objective of this study is to investigate parameters which significantly affect the CFPP performance using HR deviations. The baseline or target values are obtained from the plant commissioning manuals and the Performance Guarantee Test (PGT). It is found that at the operating baseload, the most significant negative HR deviation is for the Rotary Air Heater (RAH) gas exit temperature with a negative HR deviation of -137.9 kJ/kWh leading to an annual loss of RM8.8 million at ACP of RM12/GJ while the superheater and reheater spray flows are contributing least to the HR deviation. The HR deviations analysis highlights the impact of parameters affecting the performance and the ranking of key parameters which affect the HR of the CFPP the most significantly which enables plant operations and maintenance teams to focus on such parameters to mitigate financial losses. The third objective of this study, which is conducting economic analysis of the of the CFPP with regard to TCHR analysis and HR deviation analysis based on the Applicable Coal Price (ACP). The influence of the ACP price towards daily losses or gains has been thoroughly analysed for key performance parameters and it is evident that as the ACP increases, the daily losses increase as well for parameters with negative HR deviation thus it is crucial for plant personnel to be more vigilant on monitoring and mitigating negative HR deviations to minimise monetary losses.